PENGARUH PERACUNAN TRIKLOPIR DAN POLA PENGGERGAJIAN TERHADAP SIFAT PENGGERGAJIAN KAYU RASAMALA (ALTINGIA EXCELSA NORONHA) - Osly Rachman; Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The objective of this study is to determine the sawing properties of triclopyr poisoned rasamala logs compared to the girdled and normal ones. The effect of sawing pattern on sawing properties were also observed.The log samples used in this experiment comprise of 18 pieces which were collected from three different groups of tree (poisoned and girdled in one year periode, and control). Six logs of each group were sawn in two sawing patterns, namely live sawing and semi-quarter sawing. Parameters of sawing observed include recovery, productivity, power con- sumption, and sawn timber defects, particulary splits and bowing.The results of study revealed that moisture content of poisoned logs was 20% lower than the normal one. Mean-while, both moisture content of girdled logs and poisoned ones are not significantly diferent. Poisoning treatment on rasamala trees in comparison to girdled and normal ones did not show significant difference in any sawing properties, except sawing productivity. The sawing recovery, power consumption, splits and bowing of sawn timber were 62%; 32.37 watt sec./cm2, 5.21 cm and 3.91 cm, respectively. The live sawing could increase the pro- ductivity as much as 0.18 m3 /hour higher than semi-quarter sawing.